2018
DOI: 10.1097/sla.0000000000002480
|View full text |Cite
|
Sign up to set email alerts
|

Pylorus Resection Does Not Reduce Delayed Gastric Emptying After Partial Pancreatoduodenectomy

Abstract: German Clinical Trials Register DRKS00004191.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 32 publications
1
29
1
Order By: Relevance
“…In this present study, PRPD was significantly decreasing the DGE rate compared to PPPD (20.0% vs. 48.0%), respectively. The DGE rate in the PRPD groups was lower when compared to the results from the latest RCTs 20 (overall DGE for PRPD group=31.2%), which investigated the effect of pylorus resection to DGE outcomes. The duration of the NG tube requirement in PRPD groups was significantly shorter when compared to PPPD groups (1 day vs. 3 days).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In this present study, PRPD was significantly decreasing the DGE rate compared to PPPD (20.0% vs. 48.0%), respectively. The DGE rate in the PRPD groups was lower when compared to the results from the latest RCTs 20 (overall DGE for PRPD group=31.2%), which investigated the effect of pylorus resection to DGE outcomes. The duration of the NG tube requirement in PRPD groups was significantly shorter when compared to PPPD groups (1 day vs. 3 days).…”
Section: Discussioncontrasting
confidence: 57%
“…The pathogenesis of DGE is still unclear. Many factors were reported to increase the risk of DGE, for examples general preoperative condition, body mass index 20 , obstructive jaundice, technical aspect (preservation of pylorus, ante colic gastrojejunostomy) and postoperative complications (sepsis, intraabdominal collection). There are a lot of potential, physiologic changes following PD, especially the removal of the duodenum, and alterations in the normal path of the gastrointestinal flow were considered to increase DGE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the most recent literature did not clearly demonstrated the potential impact of pylorus preserving PD on the incidence of delayed gastric emptying (DGE). A recent randomized controlled trial [35] comparing PD with pylorus-resecting or pyloruspreserving did not showed significant difference in DGE rate. Finally, a recent metaanalysis [36] showed superiority for pylorus-resecting pancreaticoduodenectomy regarding DGE when all studies are included.…”
Section: Discussionmentioning
confidence: 89%
“…In general, surgical procedures influenced DGE, indicating the superiority of pylorus resection, 7 antecolic gastrojejunostomy or duodenojejunostomy reconstruction, 8 Braun anastomosis, 9 Billroth II reconstruction 10,11 and side-to-side gastrojejunostomy. 12,13 However, recent studies including a meta-analysis reported conflicting findings, [2][3][4][14][15][16] resulting in a lack of evidencebased effective procedures that decrease DGE consistently. Few studies have focused on pharmacological treatment for DGE after PD.…”
Section: Introductionmentioning
confidence: 99%